Inhibition of alveolar Na transport and LPS causes hypoxemia and pulmonary arterial vasoconstriction in ventilated rats - Davieds, Bodo; Gross, Julian; Berger, Marc Moritz; Baloğlu, Emel; Bärtsch, Peter; Mairbäurl, Heimo (Physiological reports, 2016)
Oxygen diffusion across the alveolar wall is compromised by low alveolar oxygen but also by pulmonary edema, and leads to hypoxemia and hypoxic pulmonary vasoconstriction (HPV). To test, whether inhibition of alveolar fluid reabsorption results in an increased pulmonary arterial pressure and whether this effect enhances HPV, we established a model, where anesthetized rats were ventilated with normoxic (21% O2) and hypoxic (13.5% O2) gas received aerosolized amiloride and lipopolisaccharide (LPS) to inhibit alveolar fluid reabsorption. Right ventricular systolic pressure (RVsP) was measured as an indicator of pulmonary arterial pressure. Oxygen pressure (PaO2) and saturation (SaO2) in femoral arterial blood served as indicator of oxygen diffusion across the alveolar wall. Aerosolized amiloride and bacterial LPS decreased PaO2 and SaO2 and increased RVsP even when animals were ventilated with normoxic gas. Ventilation with hypoxic gas decreased PaO2 by 35 mmHg and increased RVsP by 10 mmHg. However, combining hypoxia with amiloride and LPS did not aggravate the decrease in PaO2 and SaO2 and had no effect on the increase in RVsP relative to hypoxia alone. There was a direct relation between SaO2 and PaO2 and the RVsP under all experimental conditions. Two hours but not 1 h exposure to aerosolized amiloride and LPS in normoxia as well as hypoxia increased the lung wet-to-dry-weight ratio indicating edema formation. Together these findings indicate that inhibition of alveolar reabsorption causes pulmonary edema, impairs oxygen diffusion across the alveolar wall, and leads to an increased pulmonary arterial pressure.
Gesehen am 06.05.2020